A WEBSITE FOR PT. GOLDFINDO INTIKAYU PRATAMA: A WAY TO PROMOTE THE COMPANY’S PRODUCTS TO INCREASE ITS CUSTOMERS - Citra Kristiani; Jusuf I Ibrahim (Institute of Research and Community Outreach - Petra Christian University, 2016)
PT. Goldfindo Intikayu Pratama is located at Jl. Kepatihan Industri 7, Menganti, Gresik. It is a manufacturer and exporter of many kinds of products like desks, drawers, cupboards, chairs, and tables. This company mostly exports its products to importers or wholesalers in the United States. The problem of this company is the decreasing sales volume from its current customers. To solve this problem, this company needs a promotional tool, a website. This can be a good solution for the company to be known by many people in the world, because a website can be reached globally. The parts of the website are Home, About Us, Processing, Products, Clients, and Contact Us. By having a website, PT Goldfindo will be able to deliver information about the company itself and its products, to reach broader target markets, and to build its professional image.